Boriding kinetics of Fe2B layers formed on AISI 1045 steel - Zuno-Silva J.; Ortiz-Domínguez M.; Keddam M.; Elias-Espinosa M.; Damián-Mejía O.; Cardoso-Legorreta E.; Abreu-Quijano M. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In the present work, a diffusion model was suggested to study the growth kinetics of Fe2B layers grown on the AISI 1045 steel by the pack-boriding treatment. The generated boride layers were analyzed by optical microscopy and X-ray diffraction analysis. The applied diffusion model is based on the principle of mass conservation at the (Fe2B/ substrate) interface. It was used to estimate the boron diffusion coefficients of Fe2B in the temperature range of 1123-1273 K. A validation of the model was also made by comparing the experimental Fe2B layer thickness obtained at 1253 K for 5 h of treatment with the predicted value. Basing on our experimental results, the boron activation energy was estimated as 180 kJ mol-1 for the AISI 1045 steel.